Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Ritel Alfamart - Nul hakim, Luqman (Keizai, 2023)
This study's goal is to determine how customer happiness is affected by pricing and service quality. Alfamart was selected as the research object because the population of this study is made up of all customers who have made many purchases there; a sample of 100 customers was chosen by accident sampling. A questionnaire on a 4-point Likert scale was used to collect data. The research data was tested using multiple regression analysis. The test results demonstrated that price has no effect on customer satisfaction, indicating that whether a price is high or low, it has no effect on consumer satisfaction. Customer satisfaction, on the other hand, is positively correlated with service quality, meaning that the higher the quality of the services rendered, the greater the level of customer satisfaction.